2019
DOI: 10.5114/wiitm.2019.86919
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular embolization of arterial bleeding in patients with severe acute pancreatitis.

Abstract: IntroductionSevere acute pancreatitis (SAP) has a high mortality rate of 20% to 30%, with death often resulting from hemorrhage.AimTo investigate the role of digital subtraction angiography (DSA) and endovascular embolization in the management of arterial bleeding in SAP patients.Material and methodsSeventy-six patients with SAP admitted to our hospital between January 2010 and May 2016 underwent DSA. DSA revealed arterial bleeding in 22 of these patients, who were treated with transcatheter endovascular embol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…Finally, regarding thrombotic methods, hemorrhagic pseudocysts are formed when enzymes within pancreatic fluid erode arterial walls, and the most commonly affected artery is the splenic artery (30-50%), followed by gastroduodenal (17%), and pancreaticoduodenal arteries (11%) [ 16 ]. Angiographic embolization has a success rate ranging from 79 to 100% [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, regarding thrombotic methods, hemorrhagic pseudocysts are formed when enzymes within pancreatic fluid erode arterial walls, and the most commonly affected artery is the splenic artery (30-50%), followed by gastroduodenal (17%), and pancreaticoduodenal arteries (11%) [ 16 ]. Angiographic embolization has a success rate ranging from 79 to 100% [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In one study involving 76 patients, three patients died, two from hemorrhagic shock and one from brain stem infarction secondary to coagulation system dysfunction in severe acute pancreatitis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of gelfoam alone has been described in a limited number of patients in published series on the endovascular embolization of PSA. 100 101 Kulkarni et al reported gelfoam embolization in one patient in a series of 38 patients. In the same series, gelfoam was used in combination with coils in two patients.…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…Most cases of active abdominal arterial bleeding are medically treated by correcting coagulation abnormalities or through endoscopy (7)(8)(9). Nonetheless, these methods can fail in some patients with significant bleeding, in which cases endovascular treatment is desired (3,(10)(11)(12)(13)(14). Due to its advantages of reduced morbidity and mortality, endovascular treatment using digital subtraction angiography (DSA) is now preferred over open surgery (5,11,(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%